HINDU ECO-PHILOSOPHY - Suwantana, I Gede (PANGKAJA, 2012)
Traditional Hindu environmental values and concerns have continued to influence the discourse and aligned practices of environmentalism in much of South Asia. Hinduism developed a strong moral ethos which to a large extent superseded the earlier (Vedic) view from the heavens (or of the gods) by a view as if, "from nowhere", that is, from no one particular subjective position (whether divine or human). Here the moral concept of dharma emerges as a much more abstract, authoritative and autonomous notion, but with the same normative strength that the ontological and cosmological conceptions had earlier served. The universe is seen as a most meaningful and principled moral order: human beings have a responsibility, indeed a duty, to help sustain this world thus rendered morally significant. Key words: Mother Earth, Nature, Sacred